Methodological approaches in the formation of the model of informational and analytical competence of pharmaceutical specialists in the system of professional development - A. A. Kiseleva (Вестник Самарского университета: История, педагогика, филология, 2020)
n the article, the author presents a model for the formation of information and analytical competence of pharmaceutical specialists in the process of professional development, due to the need to develop the ability to conduct competent consultations of drugstore visitors to dispense over-the-counter drugs, as required by the restructuring of drugstores. During the analysis of scientific literature, the author identifies the structural components of informational and analytical competence. She analyzes the definitions of the essence of information and analytical competence, presents the developed authors concept information and analytical competence of a pharmaceutical specialist, gives its structure, which includes cognitive, need-motivational, reflective and operational-activity components, the combination of which allows a pharmaceutical specialist function efficiently in a professional space. The demand for informational and analytical competence is determined by the specifics of the activities of a pharmaceutical specialist. According to the Federal Educational Standard, this specialist carries out pharmaceutical, organizational, managerial and research activities in the course of daily professional consultations of visitors to pharmacy institutions. A specialist in the pharmaceutical profile should be able to analyze and prioritize, make decisions and take responsibility for them, have communication skills to collect information in the communication process, based on the required actions, skills and knowledge. The author describes methodological approaches to the development of a model for the formation of informational and analytical competence (cognitive, activity-based, competency-based, reflective, and functional-role). For the effective implementation of this model for the formation of informational and analytical competence, the author tests the method of blended learning.